ChemInform Abstract: Double Hetero‐Michael Addition of N‐Substituted Hydroxylamines to Quinone Monoketals: Synthesis of Bridged Isoxazolidines. Issue 50 (10th December 2013) - Yin, Zhiwei; Zhang, Jinzhu; Wu, Jing; Liu, Che; Sioson, Kate; Devany, Matthew; Hu, Chunhua; Zheng, Shengping
Abstract Quinone monoketals (I) give bridged isoxazolidines in high yields, whereas significantly lower yields are obtained by using substituted substrates (IV).